USE CLOUD СOMPUTING FOR PROFESSIONAL DEVELOPMENT OF TEACHERS (FOREIGN EXPERIENCE) - M.A. Shinenko; N.V. Soroko (Kherson State University, 2012)
Junior Researcher of Information-analytical department of pedagogical innovations, Institute of Information Technologies and Learning Tools of NAPS of Ukraine, Kyiv, e-mail: nvsoroko@rambler.ru The article presents the main characteristics of software as a service on the Internet for education leading companies Google, Microsoft, IBM. There are described some actions of these companies, which are conducted to help teachers to master cloud technology for improve the professional activities.